Depresi, Stres, dan Kecemasan Berdasarkan DASS Youth pada Siswa Sekolah Menengah Kejuruan - Donny Tri Jayadi; Fauzan Rifaldi; Muhammad Farras Hafidz; Galih Firmansyah; Chandra Yudistira Purnama; Winna Andini Handayani (Humanitas (Jurnal Psikologi), 2026)
Depression, stress, and anxiety among vocational school students are influenced by academic and social pressures, as well as differences in gender, major of study, and participation in extracurricular activities. Female students and students in certain programs are more vulnerable, while extracurricular activities can help reduce these risks. This study aims to examine differences in levels of depression, anxiety, and stress based on these factors, to provide a foundation for more appropriate interventions in supporting students’ mental health. This study involved 238 participants (F=156, Mage=16.56, SD=0.55; M=82, Mage=16.56, SD=0.55). The measurement tool used in this study, the DASS-Y, consists of 21 items across three dimensions and has a reliability coefficient of α=0.90. Data analysis employed an independent samples t-test. Results indicated significant differences in levels of depression, stress, and anxiety based on gender (p≤.001), major (p=0.010), and extracurricular activities (p=0.118). These findings suggest the need for mental health intervention approaches that account for students’ specific characteristics. Further research is recommended to examine the coping strategies used by vocational high school students in dealing with mental stress, as well as the role of social support and the school environment. Longitudinal studies and qualitative approaches can also enrich our understanding of the dynamics of their mental health over time.